Analisis Pengelolaan Sumber Daya Manusia Di Masjid Al-Mukarromah Bekasi Selatan - Mudzakky, Fachrizza; Purwanda, Eka (Universitas Islam Kadiri, 2024)
Human Resource Management in an organization is a very important factor. This research aims to analyze human resource management at the Al-Mukarromah Mosque, South Bekasi in the context of rapid cultural and technological developments. Using qualitative descriptive methods, this research identifies and evaluates various aspects of HR management implemented in the mosque. It is hoped that the findings from this study will provide insight into how HR management in this mosque adapts to rapid environmental changes and how this affects the effectiveness and prosperity of the mosque. This research provides a comprehensive overview of the challenges and strategies used to maximize the role and contribution of human resources in the context of dynamic mosque management